Chinese contemporary art in the global auction market - Archer, Anita (Anita Sarah) (Brill, 2022)
"Chinese Contemporary Art in the Global Auction Market examines the rapid rise of the global market for Chinese Contemporary art across the turn of the millennium. Focusing on key auction events, it traces the systematic and strategic role played by auction houses in promoting the work of 'avant-garde' Chinese artists, transforming them into multi-million-dollar global art superstars. Anita Archer's research into this emerging art market reveals a powerful global network of collectors, curators, dealers and auction house specialists whose understanding of the mechanics of value formation in the global art world consolidated a framework for the promotion of Chinese Contemporary art to a Western audience"-- Provided by publisherito Dewey.
Revision of the author's thesis (doctoral)--University of Melbourne, 2018, under the title: Global positioning : international auctions and the development of the Western market for Chinese Contemporary art, 1998-2012.
Keywords: Art auctions -- Western countries.; Auction houses -- Western countries.; Art, Chinese -- 20th century.; Art, Chinese -- 21st century.; Art -- Marketing.; Art chinois -- 20e siècle.; Art chinois -- 21e siècle.; Art -- Commercialisation.; Art -- Vente aux enchères -- Occident.; art market.; Art auctions; Art, Chinese; Art -- Marketing; Auction houses; Western countries; 1900-2099